Psychiatric genome-wide association study analyses implicate neuronal, immune and histone pathways - Network and Pathway Analysis Subgroup of Psychiatric Genomics Consortium (2015)
Erratum in: Corrigendum: Psychiatric genome-wide association study analyses implicate neuronal, immune and histone pathways. [Nat Neurosci. 2015]